Pentingnya Manajemen Waktu Dalam Bekerja Pada PT Asi Pudjiastuti Aviation (Susi Air) - Muhamad Riza Pahlepi; Novfitri Landong Namora Sihombing (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
Susi Air is an Indonesian airline operated by PT ASI Pudjiastuti Aviation with scheduled and charter flights. Headquartered in Pangandaran, West Java, Susi Air operates flights from 5 main bases namely in Medan (North Sumatra), Halim Perdana Kusuma (Jakarta), Central Java (Cilacap), West Java (Pangandaran and Bandung), Samarinda, and Jayapura (Papua). It was founded in late 2004 by Susi Pudjiastuti. motivation.In running its business, Susi Air must have a high level of productivity so that the relationship between the company's role and employee performance must support each other in order to achieve the desired goals. Time management is an effort to organize, supervise, plan, and control the effective use of time to achieve certain goals. The most important aspect that should be mentioned is that time management does not require a person to learn to do as many things as possible in a short period of time, but ensures that the person does what needs to be done, dealing with the thing that really needs attention. The key to achieving company goals and completing tasks with efficiency at PT Asi Pudjiastuti Aviation (Susi Air) is effective time management. However, if employees and companies are not able to manage time well, bad consequences will arise such as settlement of Late tasks, increased stress levels, and decreased productivity leading to loss of motivation.